Low Perceived Self-Efficacy Impedes Discriminative Fear Learning - Raeder, Friederike; Karbach, Lioba; Struwe, Helena; Margraf, Jürgen; Zlomuzica, Armin (Frontiers in Psychology, 2019)
Perceived self-efficacy refers to a subject’s expectation about the outcomes his/her behaviour will have in a challenging situation. Low self-efficacy has been implicated in the origins and maintenance of phobic behaviour. Correlational studies suggest an association between perceived self-efficacy and learning. The experimental manipulation of perceived self-efficacy offers an interesting approach to examine the impact of self-efficacy beliefs on cognitive and emotional functions. Recently, a positive effect of an experimentally-induced increased self-efficacy on associative learning has been demonstrated. Changes in associative learning constitute a central hallmark of pathological fear and anxiety. Such alterations in the acquisition and extinction of conditioned fear may be related to cognitive and neurobiological factors that predict a certain vulnerability to anxiety disorders. The present study builds on previous own work by investigating the effect of an experimentally-induced low perceived self-efficacy on fear acquisition, extinction and extinction retrieval in a differential fear conditioning task. Our results suggest that a negative verbal feedback, which leads to a decreased self-efficacy, is associated with changes in the acquisition of conditioned fear. During fear acquisition, the negative verbal feedback group showed decreased discrimination of fear responses between the aversive and safe conditioned stimuli (CS) relative to a group receiving a neutral feedback. The effects of negative verbal feedback on the acquisition of fear discrimination learning were indexed by an impaired ability to rate the probability of receiving a shock during acquisition upon presentation of the aversive (CS+) relative to the safe stimuli (CS-). However, the effects of low self-efficacy on discrimination learning were limited to fear acquisition. No differences between the groups were observed during extinction and extinction retrieval. Furthermore, analysis of other outcome measures, i.e., skin conductance responses and CS valence ratings, revealed no group differences during the different phases of fear conditioning. In conclusion, lower perceived self-efficacy alters cognitive/expectancy components of discrimination during fear learning but not evaluative components and physiological responding. The pattern of findings suggests a selective, detrimental role of low(er) self-efficacy on the subject’s ability to learn the association between ambiguous cues and threat/safety.